Treatment response in prostatic neoplastic lesions using CyberKnife (stereotactic body radiation therapy) (Journal of Fatima Jinnah Medical University, 2022)
Objective: To evaluate the treatment response of CyberKnife stereotactic radiotherapy in patients with prostatic neoplastic lesions.Patients and methods: This prospective observational study was conducted at Radiology and Cyberknife Robotic Radiosurgery Department of Jinnah Post Graduate Medical Centre (JPMC), Karachi from 22nd June 2019 to 21st June 2020. Males with biopsy-proven prostatic adenocarcinoma with age 55 years or more having Gleason's score of 6 to 8, clinical stage of T1 to T2C, and prostate-specific antigen (PSA) of ≤30 ng/ml were consecutively enrolled. Detailed information regarding PSA concentration, Gleason score, T stage, risk group and ADT (Androgen Deprivation Therapy) usage were noted which were given to high risk patients only for 9 months. Drop in the PSA (biochemical marker) was assessed at baseline, at 3 months and 6 months follow-up.Results: The median age of the patients was 65 years. The overall median PSA level was 2.7 (0.86-7.3) ng/ml. Majority 49 (90.7%) patients presented with T2 N0 M0 TNM status while only 5 (9.3%) patients presented with T1 N0 M0 TNM status. There were 5 (9.3%) patients with high risk, 26 (48.1%) with intermediate risk, and 23 (42.6%) with low risk. ADT was received by 5 (9.3%) patients. The median PSA at baseline was 10.1 (6.9-18.1) ng/ml which significantly drops to 1.6 (0.8-3.6) ng/ml at 3rd months, and 0.4 (0.2-1.2) at 6th months (p-value
Keywords: CyberKnife stereotactic radiotherapy; Response; Prostatic neoplastic lesions; Prostate-specific antigen; PSA; Androgen deprivation therapy